PERANCANGAN STRUKTUR BANGUNAN PELABUHAN MUARA ANGKE DENGAN PRECAST SEISMIC STRUCTURAL SYSTEM (PRESSS) - Indartono Rivai; Bayu Widianto (FTSP Universitas Jayabaya, 2021)
The Development on innovation of reinforced concrete that can resist seismic force using presstressed unbonded named PRESSS (Precast Seismic Structural System) combine with Dissipater as a splice method to transfer seismic force. PRESSS introduced in Indonesia by Ir. Hari Nugraha Nurjaman the Chairman of Ikatan Ahli Pracetak dan Prategang Indonesia or known as IAPPI.This study have a purpose to know the optimum dimensional of the structure element and to know detailing of Precast Seismic Structural System (PRESSS) structure at Pelabuhan Muara Angke Project. The internal force of building is analysed by using software ETABS with spectrumresponse method for the seismic load and also being control by using manual calculation refer to National Indonesia Standard Code about Building Reinforced Concrete Structural 2847-2019 (SNI 2847-2019) and National Indonesia Standard Code about Guidance to Design Seismic Load (SNI 1729-2019). Sub-Structure / Foundation internal force calculated with using software LPILE and controlled by manual calculation. The Results of analysis is dimension of structural slab 150 mm using D13-200 rebar two ways system. Dimension of structural beam is 300x600 mm using longitudinal rebar 2D16 (on the middle) and 3D16 (on the end), using 3 pcs of strand withdiameter 0,6 inch, the transversal rebar is D10-150 (on the middle) and D10-100 (on the end). Dimension of structural coloumn is 400x700 mm using longitudinal rebar 10D25, the transversal rebar D10-150 (on the middle) and D10-100 (on the end). Dimension of structural pile foundation is 600 mm type A1 with depth 16 meters. Dimension of structural pilecap is 1400x2900 mm with thickness 800 mm using top longitudinal rebar D16-200 and bottom longitudinal rebar D22-200.